Pengaruh Pencampuran Serat Serabut Kelapa Pada Tanah Lempung Terhadap Nilai CBR dan Kuat Geser - Damara, B. (Tadulako University, 2025)
This research aims to investigate the influence of coconut fiber incorporation on clay soil in terms of its California Bearing Ratio (CBR) and shear strength. The study involved collecting clay samples from a specific location and blending them with varying percentages of coconut fibers. Laboratory experiments were carried out to assess the CBR and shear strength of both untreated clay and clay mixed with different fiber fractions. The laboratory results revealed an improvement in CBR from the original clay value of 5.59% to 6.1% with 0.2% fiber addition, 6.64% with 0.4%, and 7.34% with 0.6%. These results indicate a consistent increase without any decline. Additionally, the shear strength test showed a 0.2% improvement, with the optimal shear strength achieved at a 0.2% fiber composition, reaching 1.0588%. The inclusion of coconut fibers significantly enhanced the CBR of the clay. The study also identified the optimal fiber fraction required to maximize CBR improvement. Moreover, the addition of coconut fibers boosted the shear strength, making this method useful for civil engineering projects such as road stabilization, foundation reinforcement, and other construction activities in areas with clay soil. This study highlights the potential of coconut fibers as a cost-effective and sustainable reinforcement material for clay soil in civil construction, offering both economic and environmental benefits to the construction industry